Ultrasound-Assisted Rhytidectomy Including Sub-SMAS and Subplatysmal Dissection - Gentile, Richard D. (Facial Plastic Surgery, 2020)
Energy-based facelifting techniques are a relatively new genre of surgery. In this approach, the energy-based device—whether laser, radiofrequency plasma, or ultrasound—can be used in the superficial plane to elevate skin flaps before performing more traditional facelift techniques involving the superficial musculoaponeurotic system (SMAS) or platysma. The initial reports of utilizing fiber lasers as surgical tools date back to approximately 2007 and initial lipolasers were used to elevate facial skin flaps. The other energy-based devices were also tested. The author has probably the largest series of energy-based facial rejuvenation procedures, having performed over 3,000 of these procedures. The advantages of laser-assisted rhytidectomy include hemostasis, facilitated dissection in areas hard to elevate conventionally such as nasolabial folds or distal neck and the remodeling and tightening of tissue that results from the activation of the wound healing cascade of neocollagenesis and wound contraction. The author currently has a preference for energy device used during rhytidectomy and it is a high frequency ultrasound energy delivered by a five-ring 2.9- and 3.7-mm probe. The use of the ultrasound dissector in both superficial and deep procedures is highlighted in this article with emphasis on its use for deep cervicoplasty and subplatysmal procedures as well as sub-SMAS elevations of the facial deep plane.
Keywords: rhytidectomy; fiber laser; helium plasma; ultrasound; Vaser